2012
DOI: 10.1038/oncsis.2012.4
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of subcellular distribution and oncogenic potential of nucleophosmin by plakoglobin

Abstract: Nucleophosmin (NPM) is a nucleolar phosphoprotein that is involved in many cellular processes and has both oncogenic and growth suppressing activities. NPM is localized primarily in nucleoli but shuttles between the nucleus and the cytoplasm, and sustained cytoplasmic distribution contributes to its tumor promoting activities. Plakoglobin (PG, γ-catenin) is a homolog of β-catenin with dual adhesive and signaling functions. These proteins interact with cadherins and mediate adhesion, while their signaling activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 68 publications
5
17
0
Order By: Relevance
“…4A). Also, plakoglobin may play a role in regulating the subcellular distribution of p53 as was recently demonstrated for NPM (Lam et al, 2012), since there was considerably more p53 in the nuclear fractions of SCC9-PG cells compared with SCC9 cells (compare Fig. 3,IB: p53).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…4A). Also, plakoglobin may play a role in regulating the subcellular distribution of p53 as was recently demonstrated for NPM (Lam et al, 2012), since there was considerably more p53 in the nuclear fractions of SCC9-PG cells compared with SCC9 cells (compare Fig. 3,IB: p53).…”
Section: Discussionsupporting
confidence: 60%
“…In contrast, plakoglobin has often been associated with tumor/metastasis suppressor activity, although the mechanisms underlying this activity remain unclear. A number of studies have suggested that plakoglobin decreases cell proliferation, migration and invasion and induces apoptosis (Simcha et al, 1996;Parker et al, 1998;Pantel et al, 1998;Charpentier et al, 2000;Winn et al, 2002;Rieger-Christ et al, 2005;Yin et al, 2005;Dusek et al, 2007;Kanazawa et al, 2008;Närkiö-Mäkelä et al, 2009;Todorović et al, 2010;Aktary et al, 2010;Aktary and Pasdar, 2012;Bailey et al, 2012;Holen et al, 2012;Franzen et al, 2012;Lam et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…PG has also been reported to be downregulated in esophageal cancer in which it is associated with a decrease in the Triton-X 100 insoluble pool of E-cadherin and desmocollin-2 and decreased E-cadherin at the cell membrane, suggesting decreased cell-cell adhesion (Fang et al 2014). The nucleolar phosphoprotein nucleophosmin interacts directly with PG in MDA-MB-231 carcinoma cells and PG expression inhibits nucleophosmin-mediated cell growth and invasion, potentially through the regulation of its subcellular localization (Lam et al 2012). …”
Section: Plakoglobinmentioning
confidence: 99%
“…In addition to TCF/LEF, plakoglobin is reported to associate with p53 and coregulate some p53 target genes (Aktary, Kulak, Mackey, Jahroudi, & Pasdar, 2013), as well as to associate with other proteins having nuclear activity (Aktary & Pasdar, 2013; Lam et al, 2012). Certain mutations in human desmosomal proteins, including desmosomal cadherins (e.g., desmoglein2 and desmocollin2), reduce plakoglobin’s junctional association, enhance its nuclear localization, and thereby contribute to the heart pathology arrhythmogenic right ventricular cardiomyopathy (ARVC) (Garcia-Gras et al, 2006).…”
Section: The Other Cateninsmentioning
confidence: 99%